Rose Bertelli Braunstein e a Criação do Bacharelado em Percussão do Curso de Música da UFSM - Goulart, Gilmar da Silva (2019)
The aim of this research was the rescuing of part of the history of the Music Course of the Federal University of Santa Maria, the first school of the Center of Arts and Letters. The part investigated was the Bachelor degree of Percussion, which began its activities in 1980, being the first in Southern Brazil, and the second one in a higher education institution in Brazil, adopting as its main strategy interviews with the central character in the creation of Percussion as part of the Music School, professor Rose Mari Bertelli Braunstein, in order to search for photographic and documentary material to complement the facts narrated by her. In addition to the interviews, Professor Braunstein provided a wealth of documentary material, including photos, concert programs, catalogs, newspapers clippings, which added weight to this story. Other faculty members were interviewed, as they are witnesses of the years which lead to the implementation of the percussion and its instruments, in the 1970s of the 20th century. The choosing of this subject presents the seriousness with the actions of preservation of the institution’s history, to avoid the disappearance and oblivion of facts and their characters involved, and also to provide research material for future generations. The research stages were: a) interviews with Professor Rose Braunstein, from which the chronology of the Percussion beginnings were established; b) search of Braunstein’s personal collection, selecting the existing material according to the historical importance of each photo album, clippings, and handwritten and mimeographed material; c) interviews with retired faculty members within and without UFSM, who brought personal testimonies that enriched the narrative; d) search for official and institutional documentation, in the form of laws, letters, certificates, etc., all analyzed and cataloged chronologically and by area of inclusion in history; e) search for the material that records the students graduated from the course over these almost 40 years, within the files of the Percussion Laboratory and by contact with these former students. As a way of conclusion, the presentation of the interviews in the form of a historical chronological account – with a brief introduction to the history of percussion and the history of the institution itself – seeks to place the Bachelor of Percussion degree in a broader, not geographically isolated context, especially related to the world connected by the world network of the second decade of the 21st century.